2016
DOI: 10.4414/smw.2016.14296
|View full text |Cite
|
Sign up to set email alerts
|

False positive dengue NS1 antigen test in a traveller with an acute Zika virus infection imported into Switzerland

Abstract: We report the first case of an acute Zika virus infection imported into Switzerland by a traveller returning from Canoa Quebrada, Ceará state, in the north-eastern part of Brazil. Due to a false positive dengue virus NS1 antigen test, IgG antibody seroconversion and a suggestive clinical picture,an acute dengue fever was initially considered. However, because of lack of specific IgM-antibodies, stationary IgG antibody titre and a negative dengue virus PCR test result, a dengue virus infection was excluded and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 0 publications
2
50
0
4
Order By: Relevance
“…The test result was reagent in one case, showing cross-reactivity between dengue and Zika. Serological cross-reactivity between ZIKV and DENV has been observed in earlier studies [5,48]. This cross-reactivity leads to the misdiagnosis of dengue because of the similarity of the clinical symptoms in addition to serological cross-reactivity.…”
Section: Discussionmentioning
confidence: 85%
“…The test result was reagent in one case, showing cross-reactivity between dengue and Zika. Serological cross-reactivity between ZIKV and DENV has been observed in earlier studies [5,48]. This cross-reactivity leads to the misdiagnosis of dengue because of the similarity of the clinical symptoms in addition to serological cross-reactivity.…”
Section: Discussionmentioning
confidence: 85%
“…Gyurech et al ( 5 ) reported false-positive test results for dengue NS1 antigen in a patient with acute Zika virus infection. Of the 3 NS1 tests used in that study, only the SD Bioline Dengue Duo (Standard Diagnostics, Inc., Gyeonggi-do, South Korea) showed positive results for 3 of 4 sequential serum samples from the patient.…”
mentioning
confidence: 99%
“…As we have demonstrated, low cross-reactivity can be used to accurately distinguish between different viral strains, which can have implications for treatment options. Additionally, low cross-reactivity is important in identifying between a novel virus and other closely related viruses before optimal antibodies are developed, as was initially the case in distinguishing Zika virus from other Flaviviridae such as dengue fever, leading to public health challenges during the early stages of the recent Zika outbreak (23).…”
Section: Discussionmentioning
confidence: 99%